TEACHERS’ AND PARENTS’ COOPERATION ROLE WITHIN PROVISION OF PEDAGOGICAL PROCESS AT SPECIAL EDUCATION - Prudnikova, Ilga; Cernova, Emilija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
In the article, the cooperation topicality is justified as well as teachers’ and parents’ of pupils with moderate and severe intellectual disabilities cooperation role within pedagogic process. The authors of the article define the approach in the base of which there is teachers’ and pupils parents’ cooperation in development of individual education programs. Thanks to which the abilities of the pupils of for pupils with moderate and severe intellectual disabilities are discovered and used as well as the need of these pupils to learn to act themselves is promoted . In the result of the empiric research, it is established that, in the evaluation of all the respondents, the indices over the research have changed with positive dynamics. This certifies that the society influences positively the pupils activities who are involved into the research.